Particleboard properties from 3 years old Petai Belalang / Muhamad Muaz Abdul Aziz - Abdul Aziz, Muhamad Muaz (Faculty of Applied Sciences, 2016)
The growing demand for wood-based panels has led to continuous efforts to find new resources as alternative raw materials without depending on the decreasing supply of rubberwood. Petai belalang, or Leucaena leucocephala, was chosen in the manufacture of particleboard with urea formaldehyde (UF) resin as a binder. The boards were produced at three density levels of 500, 600 and 700 kg m-3 with 12% of resin content. This study evaluated the mechanical and physical properties of the petai belalang particleboard. The tests were conducted according to European standards. The mechanical properties tested were modulus of rupture (MOR), modulus of elasticity (MOE) in bending and internal bond (18). Thickness swelling (TS) and water absorption (WA) were tested for physical properties. Results indicated that the strength properties of the boards improved with increased board density. Particle board with density of 700 kg m- met part of the strength requirement, which suggests a possible application of this board in the production of furniture components.